Guaranteeing Desirable Futures: What Schools Offer to Prospective Students When in Mutual Competition - Westergren Jakob; Schunnesson Jonathan (Journal of Organizational Sociology)
In this article we argue that organizational research on competition has left the relation between organizations and consumers largely unaddressed. While marketing scholars have explored how individual organizations try to manipulate the relation with specific groups of consumers, less has been said about how competing organizations collectively form and influence their relation with consumers. This is especially the case in contexts of public services provision, such as education. To explore this relation, we examine how upper secondary schools in a quasi-market fictionalize their offerings to influence students’ desire. By analyzing 117 school descriptions from Stockholm’s (Sweden) upper secondary school market, we identify four ideal types of fictionalized offerings: The Doorman, The Role Model, The Butler, and The Gardener. These fictionalizations perpetuate two consumer fictions, namely desirable futures and identity realization. Through these fictions, prospective students are invited to realize their supposedly incomplete selves. Our research contributes to the organizational study of competition by showing that schools respond to competition by reinforcing a consumption rationality, potentially shaping students’ desire for certain educational qualities. Additionally, we contribute to critical educational research by questioning the assumption that competition fosters innovation.